Overview of eutrophication-related events and other irregular episodes in Slovenian Sea (Gulf of Trieste, Adriatic sea) - Turk, Valentina (Annales. Series historia naturalis, 2007)
Eutrophication is one of the important drivers of marine ecosystem degradation and is a particularly evident problem near the centre of human population. Although advances have been made during the past 30 years, eutrophication remains one of the primary problems affecting coastal marine ecosystems...
Keywords: Adriatic Sea; evtrofikacija; Gulf of Trieste; Jadransko morje; severni Jadran; Tržaški zaliv